(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2013)
Forty advanced breeding lines of rice were studied during T Aman season (rainfed ecosystem) for finding out selection indices, variability and character association for grain yield and its components. All the tested characters were found showing significant variation. The highest genotypic, environmental and phenotypic variances were found in filled grains/panicle followed by plant height. High heritability associated with high genetic advance were obtained in panicles/hill, plant height, filled grains/panicle, 1000-grain weight and grain yield. Genotypic correlation coefficients were higher than the corresponding phenotypic correlation coefficients in most of the cases. Panicle length, panicles/hill and filled grains/panicle showed significant positive correlation with grain yield. Path analysis revealed that filled grains/panicle, panicles/hill and 1000-grain weight had positive and highest direct effects on grain yield. Moreover, panicle length had highest indirect effect on grain yield through filled grains/panicle. Discriminant function analysis revealed that a progressive increase in the efficiency of selection was observed with the inclusion of additional character in the selection index. Among the single variable indices, filled grains/panicle showed maximum relative efficiency over the straight selection for grain yield. The highest relative efficiency was observed with index involving seven characters, days to maturity + panicle length + panicles/hill + plant height + filled grains/panicle + 1000-grain weight + yield (t/ha). However, some of 3-traits, 4- traits, 5- traits, and 6- traits indices were also equally good. DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17015